Potential of Glutathione Antioxidant in the Hippocampus Repair: Preliminary Study on Bioactive Materials Antiaging of Snakehead Fish (Channa striata) in Animal Models of Aging - Sunarno Sunarno (Chemical Engineering Diponegoro University, 2015)
Snakehead fish meat contains active ingredients with anti-aging potential that serves as a precursor of glutathione. The ability of glutathione as an antiaging opportunities in the utilization of fish meat, especially snakehead fish. Snakehead fish meat contains several important amino acids, such as glutamine, cysteine​​, and glycine so the potential to be developed for the production of food that is nutritious and healthy. This study examines the essential amino acid composition of the antioxidant glutathione precursors found in snakehead fish from Rawa Pening Central Java to increase glutathione in the body and brain. The results showed that every 100g of snakehead fish meat from Rawa Pening containing glutamine (32.39%), cysteine ​​(6.61%), and glycine (9.69%). Snakehead fish meat extract given at a dose of 30 ml/kg/day in both types of animal models of aging effect on the increase in the content of glutathione and glutathione precursors, both in blood and hippocampus. Increased glutathione precursor of the most high to low, respectively glutamine, glycine, and cysteine​​. Availability of essential amino acids can support increased glutathione in the brain. This is indicated by an increase in glutathione hippocampus in both animal models, both on chronological aging or aging due to oxidative stress, respectively (0.822 and 0.359) mol/g bb compared to control tissue.